Health service needs and perspectives of a rainforest conserving community in Papua New Guinea's Ramu lowlands: a combined clinical and rapid anthropological assessment with parallel treatment of urgent cases - Middleton, Jo; Colthart, Gavin; Dem, Francesca; Elkins, Alice; Fairhead, James; Hazell, Richard J; Head, Michael G; Inacio, Joao; Jimbudo, Mavis; Jones, Christopher Iain; Laman, Moses; MacGregor, Hayley; et al. (BMJ open, 2023)
OBJECTIVES: Determine community needs and perspectives as part of planning health service incorporation into Wanang Conservation Area, in support of locally driven sustainable development. DESIGN: Clinical and rapid anthropological assessment (individual primary care assessments, key informant (KI) interviews, focus groups (FGs), ethnography) with treatment of urgent cases. SETTING: Wanang (pop. c189), a rainforest community in Madang province, Papua New Guinea. PARTICIPANTS: 129 villagers provided medical histories (54 females (f), 75 males (m); median 19 years, range 1 month to 73 years), 113 had clinical assessments (51f, 62m; median 18 years, range 1 month to 73 years). 26 ≥18 years participated in sex-stratified and age-stratified FGs (f<40 years; m<40 years; f>40 years; m>40 years). Five KIs were interviewed (1f, 4m). Daily ethnographic fieldnotes were recorded. RESULTS: Of 113 examined, 11 were 'well' (a clinical impression based on declarations of no current illness, medical histories, conversation, no observed disease signs), 62 (30f, 32m) were treated urgently, 31 referred (15f, 16m), indicating considerable unmet need. FGs top-4 ranked health issues concorded with KI views, medical histories and clinical examinations. For example, ethnoclassifications of three ((A) 'malaria', (B) 'sotwin', (C) 'grile') translated to the five biomedical conditions diagnosed most ((A) malaria, 9 villagers; (B) upper respiratory infection, 25; lower respiratory infection, 10; tuberculosis, 9; (C) tinea imbricata, 15) and were highly represented in declared medical histories ((A) 75 participants, (B) 23, (C) 35). However, 29.2% of diagnoses (49/168) were limited to one or two people. Treatment approaches included plant medicines, stored pharmaceuticals, occasionally rituals. Travel to hospital/pharmacy was sometimes undertaken for severe/refractory disease. Service barriers included: no health patrols/accessible aid post, remote hospital, unfamiliarity with institutions and medicine costs. Service introduction priorities were: aid post, vaccinations, transport, perinatal/birth care and family planning. CONCLUSIONS: This study enabled service planning and demonstrated a need sufficient to acquire funding to establish primary care. In doing so, it aided Wanang's community to develop sustainably, without sacrificing their forest home.
Keywords: deštný prales; dospělí; lidé; Papua Nová Guinea; Female; mužské pohlaví; zdravotnické služby; Papua New Guinea; Male; Rainforest; Health Services; Adult; ženské pohlaví; Humans